Sn species modified mesoporous zeolite TS-1 with oxygen vacancy for enzyme-free electrochemical H2O2 detecting. Issue 47 (17th November 2022) - Xue, Fengfeng; Qin, Ruomeng; Zhu, Runwei; Zhou, Xiaoxia
Abstract : Sn species modified zeolite TS-1 with a unique mesopore structure (Sn-TS-1) and rich oxygen vacancy defects has been designed, which can be used as an enzyme-free electrochemical sensor for H2 O2 detection. Abstract : Sn species modified zeolite TS-1 with a unique mesopore structure (Sn-TS-1) and rich oxygen vacancy defects has been designed via a sol–gel method and an ion-exchange process, which can be used as an enzyme-free electrochemical sensor for H2 O2 detection. The resultant composite Sn-TS-1 has a high BET surface area of 191 cm 2 g −1, fast electron transfer, rich oxygen vacancies, and abundant active sites, showing super performance in H2 O2 reduction with a low detection limit (0.27 μM, S/N = 3). The current is linear with H2 O2 concentration from 1 to 1000 and 1000 to 11 000 μM, and the corresponding sensitivities are 360.4 and 80.44 μA mM −1 cm −1, respectively. More importantly, this Sn-TS-1 sensor also shows excellent anti-interference ability and stability. This work provides a new idea for an enzyme-free sensor for H2 O2 detection in biological environments, which has promising potential in point-of-care (POC) testing for H2 O2 .